Structural analysis of mitochondrial dynamics: from cardiomyocytes to osteoblasts ; a critical review - Mendelsohn, Daniel H.; Schnabel, Katja; Mamilos, Andreas; Sossalla, Samuel; Pabel, Steffen; Dürr, Georg Daniel; Keller, Karsten; Schmitt, Volker H.; Barsch, Friedrich; Walter, Nike; Wong, Ronald Man Yeung; El Khassawna, Thaqif; et al. (International journal of molecular sciences, 2022)
Mitochondria play a crucial role in cell physiology and pathophysiology. In this context, mitochondrial dynamics and, subsequently, mitochondrial ultrastructure have increasingly become hot topics in modern research, with a focus on mitochondrial fission and fusion. Thus, the dynamics of mitochondria in several diseases have been intensively investigated, especially with a view to developing new promising treatment options. However, the majority of recent studies are performed in highly energy-dependent tissues, such as cardiac, hepatic, and neuronal tissues. In contrast, publications on mitochondrial dynamics from the orthopedic or trauma fields are quite rare, even if there are common cellular mechanisms in cardiovascular and bone tissue, especially regarding bone infection. The present report summarizes the spectrum of mitochondrial alterations in the cardiovascular system and compares it to the state of knowledge in the musculoskeletal system. The present paper summarizes recent knowledge regarding mitochondrial dynamics and gives a short, but not exhaustive, overview of its regulation via fission and fusion. Furthermore, the article highlights hypoxia and its accompanying increased mitochondrial fission as a possible link between cardiac ischemia and inflammatory diseases of the bone, such as osteomyelitis. This opens new innovative perspectives not only for the understanding of cellular pathomechanisms in osteomyelitis but also for potential new treatment options.
Published: 20 April 2022
This article belongs to the Special Issue Inflammation and the Musculoskeletal System
Gesehen am 27.06.2022